Hearing new voices: Re-viewing Youth Justice Policy through Practitioners' Relationships with Young People. (April 2014) - Drake, Deborah H.; Fergusson, Ross; Briggs, Damon B.
The relationship between young people and practitioners is the centrepiece of youth justice provision, yet little research-based knowledge has accumulated on its minutiae. After reviewing reforms affecting professional discretion, the article draws on the concepts of dyadic relationships and praxis to reinvigorate a research agenda aimed at delineating a more nuanced understanding of practice relationships. Drawing on practice wisdom from across related social work fields, we argue that centralizing the practitioner-young person relationship remains the key to successful practice and thus needs greater, more detailed research attention. These claims are supported with a number of pilot interviews with youth justice workers about successful interventions that complement and extend related studies. The article concludes with suggestions for research to enable joint activity between young people and practitioners to 'rethink' youth justice.